Reliability and validity of a talent identification test battery for seated and standing Paralympic throws - Spathis, J. G.; Connick, M. J.; Beckman, E. M.; Newcombe, P. A.; Tweedy, S. M. (Journal of Sports Sciences, 2015)
Paralympic throwing events for athletes with physical impairments comprise seated and standing javelin, shot put, discus and seated club throwing. Identification of talented throwers would enable prediction of future success and promote participation; however, a valid and reliable talent identification battery for Paralympic throwing has not been reported. This study evaluates the reliability and validity of a talent identification battery for Paralympic throws. Participants were non-disabled so that impairment would not confound analyses, and results would provide an indication of normative performance. Twenty-eight non-disabled participants (13 M; 15 F) aged 23.6 years (±5.44) performed five kinematically distinct criterion throws (three seated, two standing) and nine talent identification tests (three anthropometric, six motor); 23 were tested a second time to evaluate test-retest reliability. Talent identification test-retest reliability was evaluated using Intra-class Correlation Coefficient (ICC) and Bland-Altman plots (Limits of Agreement). Spearman`s correlation assessed strength of association between criterion throws and talent identification tests. Reliability was generally acceptable (mean ICC = 0.89), but two seated talent identification tests require more extensive familiarisation. Correlation strength (mean rs = 0.76) indicated that the talent identification tests can be used to validly identify individuals with competitively advantageous attributes for each of the five kinematically distinct throwing activities. Results facilitate further research in this understudied area.